Assessing the technical efficiency of intermodal freight transport chains using a modified network DEA approach. (June 2019) - Saeedi, Hamid; Behdani, Behzad; Wiegmans, Bart; Zuidwijk, Rob
Highlights: Presenting a modified network data envelopment analysis (NDEA) method to measure the performance of different intermodal freight transport (IFT) chains inside a freight network. Defining the relevant intermediate service to connect the performance of various divisions in an IFT chain. Formulating the modified NDEA model for the case of an IFT network consisting of IFT chains with different structures. Applying the model to a sample of European IFT network to measure the performance of the IFT network and study the sources of inefficiencies. Abstract: This paper presents a modified Network DEA model (NDEA) to measure the performance of intermodal freight transport (IFT) chains and to find the sources of inefficiencies. The model addresses two challenges in the application of NDEA to the IFT domain: first, the chains may differ in the number of divisions (i.e., transshipment/transportation activities); and second, one needs to define a relevant intermediate service. For purposes of illustration, the model is applied to a particular European IFT network for which the inefficient transport/transshipment segments are identified and discussed.